Organizational strategies for cancer screening outreach and navigation: A qualitative study - Ann M. Nguyen; Oliver Lontok; Jeanne M. Ferrante; Anita Y. Kinney (Preventive Oncology & Epidemiology, 2025)
Background: The COVID-19 pandemic led to organizational changes in cancer care and prevention, including approaches to cancer screening outreach and navigation. Our study aimed to identify current strategies used by outreach and navigation teams to facilitate cancer screening.Methods: In this qualitative study, in-depth interviews (N = 11) were conducted using positive deviant sampling to recruit cancer screening outreach and navigation teams from healthcare organizations across New Jersey. The immersion-crystallization approach was used to assess emergent themes. Identified strategies were mapped to screening barriers.Results: Participants reported six key strategies to address cancer screening barriers: (1) Build and sustain a diverse, cohesive patient outreach and navigation team; (2) Personalize outreach to patients and local organizations; (3) Have a dedicated data analyst to identify and track patients; (4) Offer multiple screenings in one visit and a seamless transition to the next service; (5) Advertise incentives and opportunities that can address social determinants of health needs; and (6) Develop relationships and referral systems with local specialists and residency programs.Discussion: Cancer screening strategies have evolved through the pandemic, becoming more attuned to the patient experience. Healthcare organizations should consider investments in centralized cancer navigation and outreach and data-related infrastructure.